Synthesis, biological activity and multiscale molecular modeling studies for coumaryl-carboxamide derivatives as selective carbonic anhydrase IX inhibitors - Belma Zengin Kurt; Fatih Sonmez; Serdar Durdagi; Busecan Aksoydan; Ramin Ekhteiari Salmas; Andrea Angeli; Mustafa Kucukislamoglu; Claudiu T. Supuran (Taylor & Francis Group, 2017)
New coumaryl-carboxamide derivatives with the thiourea moiety as a linker between the alkyl chains and/or the heterocycle nucleus were synthesized and their inhibitory activity against the human carbonic anhydrase (hCA) isoforms hCA I, II, VII and IX were evaluated. While the hCA I, II and VII isoforms were not inhibited by the investigated compounds, the tumour-associated isoform hCA IX was inhibited in the high nanomolar range. 2-Oxo-N-((2-(pyrrolidin-1-yl)ethyl)carbamothioyl)-2H-chromene-3-carboxamide (e11) exhibited a selective inhibitory action against hCA IX with the Ki of 107.9 nM. In order to better understand the inhibitory profiles of studied molecules, multiscale molecular modeling approaches were used. Different molecular docking algorithms were used to investigate binding poses and predicted binding energies of studied compounds at the active sites of the CA I, II, VII and IX isoforms.